Development of a land suitability model for saffron (Crocus sativus L.) cultivation in Khost Province of Afghanistan using GIS and AHP techniques. Issue 7 (2nd July 2016) - Wali, Emal; Datta, Avishek; Shrestha, Rajendra P.; Shrestha, Sangam
ABSTRACT: In this study, we have attempted to develop a land suitability model for saffron, an agronomic crop, which is economically viable, environmentally bearable and socially equitable at Khost Province of Afghanistan. The objective was to determine different land suitability classes for saffron cultivation using Analytical Hierarchy Process (AHP) and Geographic Information System (GIS). A decision tree was developed encompassing the physical, economic and social criteria. We used the secondary data (meteorological, remote sensing) from available sources and also substantial primary data generated from soil survey, interviews and experts' opinion. A total of 30 physical and socio-economic factors were included in the analysis. The final land suitability result showed that out of the total land area of Khost Province, 1.5, 4.5, 8.6 and 85.4% areas were highly suitable, moderately suitable, marginally suitable and not suitable, respectively. This modelling approach can be applied to determine the suitability of land for other crops covering a wider geographical region of Afghanistan.